1976
DOI: 10.1159/000178729
|View full text |Cite
|
Sign up to set email alerts
|

Oestradiol Receptors in Non-Neoplastic Gynaecomastic Tissue of Phenotypic Males

Abstract: Cytoplasmic oestradiol receptors have been reported in breast tumour tissue but not in the uninvolved tissue from the same patients. Since gynaecomastic tissue is highly predisposed to neoplastic transformation, such receptors were looked for in this tissue from 13 phenotypic males of whom 6 had Klinefelter’s syndrome. High affinity saturable binding (Kd ∼ 10-10 M) of 3H-oestradiol-170 was found in the breast tissue from 12 of these patients by gel elution and dextran-coated ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

1980
1980
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
2
2
Order By: Relevance
“…Two recent attempts to review the literature (7, 8) have shown 24 out of 69 specimens (34%) to be ER-positive. It is of interest that most of the ER-positive cases (1 7 out of 19, 90%) were reported by two institutions (9,17). The figures of these two institutions differ significantly from our data as well as data published by others (6,7).…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Two recent attempts to review the literature (7, 8) have shown 24 out of 69 specimens (34%) to be ER-positive. It is of interest that most of the ER-positive cases (1 7 out of 19, 90%) were reported by two institutions (9,17). The figures of these two institutions differ significantly from our data as well as data published by others (6,7).…”
Section: Discussioncontrasting
confidence: 85%
“…As the techniques for recep tor analysis were largely identical, the reason for these discrepancies could be that different patient populations were tested. However, the data of Rajendran et al (17) do not support this assump tion as the ER analyses of this study were based on gynecomasty tissue obtained from 6 patients with Klinefelter's syndrome, which were all ER-positive and 7 specimens from patients with idiopathic gynecomasty of which 6 were ER-positive. There may be other important factors, but they remain obscure for the time being.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In Klinefelter patients the secretion of estrogens is normal (Giorgi and Sommerville -1963). Estradiol receptors in non neoplastic gynecomastia as well as in tumor tissue of Klinefelter patients have been reported (Ellison et al -1980;Leclercq et al -1976, Rajendran et al -1976. Estradiol receptors in non neoplastic gynecomastia as well as in tumor tissue of Klinefelter patients have been reported (Ellison et al -1980;Leclercq et al -1976, Rajendran et al -1976.…”
Section: Discussionmentioning
confidence: 99%